Malaria and Typhoid Fever Coinfection in the Hospital University of Bobo-Dioulasso, Burkina Faso - Sangaré Ibrahim; Sourabié Yacouba; Bazié Wilfried Wenceslas; Sirima Constant; Da Fabrice; Sanou Do Soufiane; Zoungrana Jacques; Poda Armel; Ouédraogo Abdoul Salam; Bamba Sanata (Journal of Parasite Research, 2019)
Malaria and typhoid fever are two endemic infectious diseases in developing tropical countries including Burkina Faso. There are two distinct infectious diseases with many similar clinical signs. In each sanitary area, it is important to describe the
Keywords: Malaria